Factorial and diagnostic validity of the beck depression inventory-II (BDI-II) in Croatian primary health care - Jakšić, Nenad (Array, 2013)
The aim of this study was to examine the factorial and diagnostic validity of the Beck Depression Inventory-Second Edition (BDI-II) in Croatian primary health care. Data were collected using a medical outpatient sample (N = 314). Reliability measured by internal consistency proved to be high. While the Velicer MAP Test showed that extraction of only one factor is satisfactory, confirmatory factor analysis indicated the best fit for a 3-factor structure model consisting of cognitive, affective and somatic dimensions. Receiver operating characteristics (ROC) analysis demonstrated the BDI-II to have a satisfactory diagnostic validity in differentiating between healthy and depressed individuals in this setting. The area under the curve (AUC), sensitivity and specificity were high with an optimal cut-off score of 15/16. The implications of these findings are discussed regarding the use of the BDI-II as a screening instrument in primary health care settings.